Effect of Salinities on Growth and Haematology of Pangasianodon hypophthalmus (Sauvage, 1878): Salinity impact on Growth and Haematology of P. hypophthalmus - Ramadasu Srinivasulu, Sravani; Arumugam, Balasubramanian; Tummala, Suguna; R. R., Anupama; Mohana Swapna Narra (Fishery Technology, 2024)
Pangasianodon hypophthalmus juveniles having total length of 13.35±0.14cm and body weight of 17.52±0.16g were subjected to salinity levels of 4, 9 and 14 ppt and 0ppt as control, for determining their growth and hematological changes. The highest growth in length (14.57±0.92cm) and weight (20.89±2.51g) were observed in control while the lowest length (13.90±0.46cm) and weight (19.10±1.30g) in 14ppt. The highest SGR (1.19±0.15) and PER (3.63±0.37) were observed in control while lowest SGR (0.65±0.14) and PER (1.93±0.24) in 14ppt. The highest FCR observed was (2.18±0.27) in 14ppt and the lowest (1.16±0.16) in control. High count of TLC was recorded in 14ppt (28.37±0.65 (103/μl)) and the least in control (24.52±0.81 (103/μl)). The TEC was high (2.42±0.17 (106/μl)) in control and the least (1.99±0.20 (106/μl)) in 14ppt. The Hb was high in control (9.46±0.21g/dL) while least in 14ppt (6.93±0.43 g/dL). High Ht was observed in control (29.20±0.61%) whilst the least in 14ppt (24.07±1.83%). The highest MCV was observed in the salinity of 4ppt (125.07±9.12fL) and the lowest in 9ppt (121.01±6.25fL). On contrary, the high MCHC (33.73±0.92g/dL) was observed in 9ppt and the low (28.86±1.39g/dL) in 14ppt. The present research findings concluded that though P. hypophthalmus survived upto higher salinities of 14ppt, they exhibited poor growth performance when compared to lower salinities.